High Level Resistance of Enterococcus faecium and E. faecalis Isolates from Municipal Sewage Treatment Plants to Gentamicin - M Saifi; MM Soltan Dallal; MR Pourshafie; MR Eshraghian; MR Pourmand; MH Salari; MH Shirazi (Tehran University of Medical Sciences, 2008)
Background: Enterococci are members of the normal gut flora and released into the environment via sewage outlets, where they can survive for long times. Infections with high-level gentamicin resistant (HLGR) enterococci are emerging worldwide. HLGR enterococci have developed a resistance to most antibiotics commonly used for enterococcal infections therefore; treatment of infections caused by HLGR enterococci is difficult. The present study investigated the distribution and antibiotic resistance of HLGR Enterococcus faecium and E. faecalis isolates from raw wastewater samples in Tehran.Methods: Raw wastewater samples were collected during the period from November 2006 to May 2007 at 3 sewage treatment plants located in different parts of Tehran. All 90 HLGR enterococcal isolates were identified to the species level by biochemical and PCR assays and subjected to antibiotic susceptibility testing. Results: Sixty four percent (58 of 90) of isolates were E. faecium and 29%(26 of 90) of them were E. faecalis. The highest level of antibiotic resistance was observed with erythromycin (63%), co-trimoxazole (69%) and tetracycline (92%) for E.faecalis and with erythromycin (97%), ciprofloxacin (47%), co-trimoxazole (45.5%) and tetracycline (47%) for E. faecium. Multiresistance against 3 to 4 antimicrobial was present in 27.5% and 15.5% of the isolates, respectively. Conclusion: HLGR E. faecium were more commonly found than E. faecalis. Species identification of HLGR enterococci enables us to assess species-specific antibiotic susceptibility patterns in our area. The present study reviled that HLGR E. faecalis remained more susceptible than E. faecium against the usual first-line and alternative treatments.